Risk analysis in lending: modern approaches and methods ("Journal "U". Economy. Management. Finance.", 2025)
The article examines modern approaches and methods of risk analysis in lending, focusing on the importance of effective risk management for financial institutions. The focus is on quantitative and qualitative methods for assessing credit risks, as well as new technologies such as machine learning and big data analysis. Examples of the implementation of these methods in the practice of banks and credit institutions, as well as their impact on decision-making, are investigated. In conclusion, the need to adapt approaches to rapidly changing market conditions and regulatory requirements is emphasized.
Keywords: lending; risks; risk analysis; assessment methods; machine learning; big data; risk management